2014
DOI: 10.1080/10826076.2013.873873
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tetracyclines Residues in Egg, Milk, and Milk Powder by Online Coupling of A Precolumn Packed with Molecular Imprinted Hybrid Composite Materials to RP-HPLC-UV

Abstract: A rapid, specific, and sensitive method was developed for determination of tetracyclines (TCs) in egg, milk, and milk powder samples by online molecularly imprinted solid-phase extraction (MISPE) coupled to a reversed-phase high-performance liquid chromatography (HPLC). A molecularly imprinted polymer hybrid composite material (MIP-HCM) was prepared using TC as the template, methacrylic acid as the functional monomer, tetraethoxysilane as inorganic precursor, and methacryloxypropyltrimethoxysilane as the coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Other methods [34][35][36][37][38][39] for detection of TCs were compared and presented in Supporting Information Table S7 to better reflect the performance of this method. Considering all aspects including sample preparation time, the recovery, LOD, and RSD, this method has some advantages over other methods.…”
Section: Methods Validationmentioning
confidence: 99%
“…Other methods [34][35][36][37][38][39] for detection of TCs were compared and presented in Supporting Information Table S7 to better reflect the performance of this method. Considering all aspects including sample preparation time, the recovery, LOD, and RSD, this method has some advantages over other methods.…”
Section: Methods Validationmentioning
confidence: 99%
“…Protein precipitation in milk and egg samples involves the use of organic solvents including acetonitrile [6,10,23,46,51], methanol [52][53][54][55] or acetone [56], as well as the combination of these solvents with acid compounds, such as trichloroacetic acid [46,[57][58][59][60][61], trifluoroacetic acid [62,63], glacial acetic acid [64][65][66], succinic acid [67,68], citric acid [23,69], formic acid [54,70], or perchloric acid [71]. Other authors have used McIlvaine-EDTA [6,[72][73][74][75][76][77][78][79], sodium citrate [10], oxalate [63], sodium succinate [80] and phosphate [81] buffers as deproteinizing agents for the treatment of these samples. Such processes are generally followed by some sample clean-up procedures.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…Although the configuration of the latter is not very common in analytical chemistry, it provides good detection limits because of the avoidance of the dilution phenomenon involved in the elution process [92]. On the other hand, most on-line SPE protocols for the determination of tetracyclines in animal-derived foods consist of SPE columns coupled with one of the following: HPLC systems [76][77][78]100,114], spectrophotometric detectors [74] or chemiluminescence [105] detectors.…”
Section: Automated Spementioning
confidence: 99%
See 1 more Smart Citation
“…Its extensive use in human disease treatment and animal husbandry is as a result of its high availability, low price and effectiveness. Residues of TC and its derivatives (tetracycline hydrochloride, oxytetracycline, doxycycline and chlortetracycline) have been reported in cattle (Aalipour et al, 2015;Kimera et al, 2015) and poultry (Abdel-Mohsein et al, 2015;Lv et al, 2015) products. Reports of TC toxicity has shown that it can cause growth inhibition of soil and water microorganisms and various stress induced dose-dependent transcriptional responses of organisms (Chang et al, 2015).…”
mentioning
confidence: 99%